Patient Education on Oral Anticoagulation - Emily M Hawes (MDPI AG, 2018)
Given the potential harm associated with anticoagulant use, patient education is often provided as a standard of care and emphasized across healthcare settings. Effective anticoagulation education involves face-to-face interaction with a trained professional who ensures that the patient understands the risks involved, the precautions that should be taken, and the need for regular monitoring. The teaching should be tailored to each patient, accompanied with written resources and utilize the teach-back method. It can be incorporated in a variety of pharmacy practice settings, including in ambulatory care clinics, hospitals, and community pharmacies.